Peterson's guide to graduate programs in the biological and agricultural sciences, 1996. - Peterson's Guides, Inc. (Princeton, N.J. Peterson's Guides, 1996)
Annual
Keywords: Universities and colleges -- Graduate work -- United States -- Directories; Agricultural education -- Canada -- Directories; Agricultural education -- United States -- Directories; Agriculture -- Education -- Canada -- Directories; Agriculture -- Education -- United States -- Directories; Biology -- Education -- Canada -- Directories; Biology -- Education -- United States -- Directories; Biology -- Study and teaching (Graduate) -- Canada -- Directories; Biology -- Study and teaching (Graduate) -- United States -- Directories; Universities and colleges -- Graduate work -- Canada -- Directories; Universities -- Canada -- Directories; Universities -- United States -- Directories